2018
DOI: 10.1016/j.arthro.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Partial Meniscectomy Versus Physical Therapy for Degenerative Meniscus Lesions: How Robust Is the Current Evidence? A Critical Systematic Review and Qualitative Synthesis

Abstract: Level II, systematic review of Level I and II studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…We found 2 systematic reviews that evaluated study quality and risk of bias for RCTs and that examined the effectiveness of APM. 58,87 Hohmann et al 58 found insufficient evidence to conclude superiority of APM or physical therapy for treating degenerative meniscal tears, owing to high risk of bias and studies being moderate to low quality. Also, the study samples were small and there was heterogeneity in eligibility criteria, outcome measures, and physical therapy protocols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 2 systematic reviews that evaluated study quality and risk of bias for RCTs and that examined the effectiveness of APM. 58,87 Hohmann et al 58 found insufficient evidence to conclude superiority of APM or physical therapy for treating degenerative meniscal tears, owing to high risk of bias and studies being moderate to low quality. Also, the study samples were small and there was heterogeneity in eligibility criteria, outcome measures, and physical therapy protocols.…”
Section: Resultsmentioning
confidence: 99%
“…43,68,73 Substantial evidence is available demonstrating no difference in clinical outcomes for APM versus conservative management for degenerative meniscal tears 1,70,77,78,106,132 ; however, the available evidence may be biased and of low quality. 58,87 Clinical outcomes tended to improve after APM and reoperation rates were low, although knee osteoarthritis is likely to develop after APM. 13,102,104 Meniscal repairs have been associated with good clinical outcomes overall, 45,81,143 and for isolated meniscal repairs there has been no difference in clinical outcomes between all-inside versus inside-out repairs.…”
Section: Discussionmentioning
confidence: 99%
“…Although several randomised controlled trials failed to demonstrate a clinically important benefit of APM over non-operative alternatives4–10 or sham surgery11 in middle-aged and older patients with symptomatic meniscal tears, these results have not led to a consistent decline in the number of APMs performed in daily practice 2 12. Common arguments for performing APM include being a difficult habit to break, being influenced by personal experiences (observational evidence), criticism of the experimental evidence (eg, low external validity) and a surgeon’s belief in being capable to identify which patient may still benefit more from surgery 13–19. Therefore, it is suggested to be up to the judgement of the treating surgeon to decide what is best for the individual patient 18…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis of randomized controlled trials 33 on APM versus nonoperative treatment for degenerative meniscal tears in adults showed small, although statistically significant, favorable results of APM up to 6 months for physical function and pain, but no differences were found after 12-month to 24-month follow-up. Another recent critical systematic review 13 on APM versus physical therapy for degenerative meniscal lesions found that the quality of the available published literature was not robust enough at this time to support claims of superiority for either alternative, and both APM and physical therapy could be considered reasonable treatment options for this condition. Another recent critical review of the published literature reported that valid conclusions cannot be drawn with regard to the optimal treatment for meniscal tears.…”
Section: Discussionmentioning
confidence: 99%
“…Some randomized trials reported that as high as 19% to 35% of patients allocated to physical therapy crossed over to APM during the first year of follow-up. 24 Thus, recent systematic reviews 13,23 concluded that APM may be considered a reasonable option for degenerative meniscal tears in selected middleaged patients, particularly if they have mild OA.…”
mentioning
confidence: 99%